MATERIAL SELECTION AND MANUFACTURING PROCESS OPTIMIZATION OF MARINE PROPELLERS - delpero, muhammad arif; Putra, Ahmadi Bintan; aminuddin, aminuddin aminuddin; hasibuan, fardin (Universitas Riau Kepulauan, 2025)
Marine propellers are essential components in ship propulsion systems, and their performance significantly impacts the overall efficiency of vessels. This paper presents a literature review on the optimization of material selection and manufacturing processes for marine propellers. The study explores the advantages and disadvantages of commonly used materials, including brass, bronze, and stainless steel, with a particular focus on their strength, corrosion resistance, cavitation resistance, and cost-effectiveness. Furthermore, the paper examines various manufacturing processes employed in propeller production, such as casting, forging, and machining, analyzing their impact on the final product's quality, precision, and performance. This review aims to provide a comprehensive understanding of the key considerations in material selection and manufacturing process optimization for marine propellers, ultimately contributing to the development of more efficient and durable propeller designs.